Caregiver coping with the mentally ill: a qualitative study. (4th March 2017) - Azman, Azlinda; Jamir Singh, Paramjit Singh; Sulaiman, Jamalludin
Abstract: Background : Mental illness is a disease that affects millions of people every year. It not only causes stress to the mentally ill patients, but also for the family members who provide them the care. The family caregivers, therefore need some form of coping strategies in dealing with their mentally ill family members. Aims : This qualitative study aims at identifying and analysing the coping strategies adopted by the family caregivers in dealing with their mentally ill family members. Method : A total of 15 family caregivers from the state of Kedah, Malaysia participated in the face-to-face semi structured interview. Results : The study findings identified an array of coping strategies used by the family caregivers, including religious coping, emotional coping, acceptance, becoming engaged in leisure activities, and the use of traditional healing to help them cope with their mentally ill members. Suggestions and conclusions : Study suggests that the family caregivers should engage themselves in social support groups to learn about and obtain the positive coping strategies used by other caregivers who have similar experiences in caring for the mentally ill. Study also suggests that they should get appropriate training from the mental health professionals in order to enhance the caregivers' coping skills.